A Case of Synchronous Malignant and Benign Granular Cell Tumor of the Vulva. (September 2021) - Baranova, Katherina; Goebel, Emily A.; McGee, Jacob; Walsh, Joanna C.
Abstract : Granular cell tumors (GCT) are rare soft tissue neoplasms, which seldom occur in the vulva. They are more commonly benign, but malignant GCT do occur. We report a case of a 50-yr-old postmenopausal woman who presented with a vulvar lesion that was diagnosed as GCT on biopsy. Imaging and clinical examination revealed an enlarged, likely positive lymph node. Pathology of the subsequently resected total deep vulvectomy specimen showed 2 histologically distinct GCTs. The larger lesion met criteria for malignancy and histologically corresponded to metastatic deposits seen in the pelvic lymph nodes. The separate smaller lesion was histologically benign. This case illustrates a malignant GCT with a synchronous, likely benign GCT both occurring in the vulva. Our case demonstrates the application of histologic criteria in the diagnosis of malignant and benign GCT with discussion on the diagnosis and treatment of this rare tumor.